NILAI MORAL DALAM NOVEL MEGALOMANIA KARYA MARHALIM ZAINI - Siti Irmawati; Elmustian Rahman; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is titled moral values in the novel megalomania by Marhalim zaini. This study aims to describe the moral values contained in the novel megalomania Marhalim zaini. The method used is descriptive method of analysis. This research date in the form of date in the form or word, phrases in sentencesor events that describe the moral value. Collection techniques by documenting and studying books that can assist in collecting date related to the problem. In the megalomania novel there are 7 noble moral values and 6 disgraceful moral values. The date analyzed by 22 date of good character.Keywords: Moral Values, Novel Megalomania.